Spironolactone inhibits the activity of the Na+/H+ exchanger in the aorta of mineralocorticoid-induced hypertensive rats. (December 2015) - Carreño, Juan E; Verdugo, Fernando J; Contreras, Felipe; Montellano, Felipe A; Veloso, Sebastian; Schalper, Kurt A; Sandoval, Mauricio; Villanueva, Sandra; Marusic, Elisa; Irarrazabal, Carlos E
Introduction: Aldosterone can induce changes in the expression or activity of Na + /H + exchanger isoform 1 (NHE–1) in vascular smooth muscle cells. We aimed to clarify whether chronic mineralocorticoid receptor activation exerts an effect on the activity of NHE–1 in the aorta of mineralocorticoid-induced hypertensive rats. Methods: Uninephrectomized male Sprague-Dawley rats received subcutaneously 10 mg/week of desoxycorticosterone (DOCA) with or without 20 mg/kg of spironolactone, or vehicle alone ( n = 20). After four weeks of treatment, the animals were sacrificed; the aorta was excised for subsequent studies, including histological analysis, RT-PCR, Western blot, measurement of NHE-1 activity and vascular contractility in the presence or absence of the selective NHE-1 inhibitor ethyl-isopropyl amiloride (EIPA). Results: Chronic DOCA treatment increased the NHE-1 activity, systolic and diastolic blood pressure, and aortic wall thickness. All these effects were prevented by co-treatment with Spironolactone ( p < 0.05). Phenylephrine-induced vascular contractility was significantly reduced in the DOCA group when EIPA was added in the media ( p < 0.05). No significant differences in NHE-1 mRNA or protein levels were detected between groups. Conclusions: Chronic DOCA administration induced functional and morphological alterations in the rat aorta that are partially explained by enhanced NHE-1 activity and prevented by spironolactone. However, we did not observe changes in the NHE-1 transcript or protein levels, suggesting that the effect may be due to post-transcriptional modifications induced by mineralocorticoid receptor activation.